2021
DOI: 10.1126/sciadv.abj9111
|View full text |Cite
|
Sign up to set email alerts
|

Misexpression of genes lacking CpG islands drives degenerative changes during aging

Abstract: Disrupted nuclear architecture triggers misexpression of genes lacking CpG islands and physiological deterioration during aging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 84 publications
(130 reference statements)
3
9
0
Order By: Relevance
“…These data support the model proposed by Lee et al [1], whereby tissue-restricted CGI-gene expressions become increasingly misexpressed during aging, contributing to loss of cellular identity, multiple aging-related pathologies, and ultimately death. Future investigations may identify a subset of CGI-gene misexpressions that can serve as an accurate and convenient measure of the rate of senescent aging at a single timepoint in adults.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These data support the model proposed by Lee et al [1], whereby tissue-restricted CGI-gene expressions become increasingly misexpressed during aging, contributing to loss of cellular identity, multiple aging-related pathologies, and ultimately death. Future investigations may identify a subset of CGI-gene misexpressions that can serve as an accurate and convenient measure of the rate of senescent aging at a single timepoint in adults.…”
Section: Discussionsupporting
confidence: 90%
“…Lee et al recently showed [1] that the misexpression of many genes lacking CpG islands (CGI-genes) increases with age in both mice and humans, is higher in patients with aging-associated diseases than in healthy age-matched controls, and is suppressed in aged mice receiving various treatments known to extend lifespan. Lee et al [1] further showed that these CGI-gene misexpressions promote inflammation and the development of degenerative changes, supporting the inflammaging theory of aging [3].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence indicates that BrdU, upon incorporation into A/T-containing DNA, destabilizes nucleosome positioning through changing DNA structure, and alters chromatin organization and gene expression with induction of cellular senescence in human cells [16][17][18][19][20][21]. Importantly, this notion is in good agreement with the recent report that misexpression of genes lacking CpG islands, which is caused by disrupted chromatin architecture, is a common feature of aged cells [34]. Given that chromatin organization regulates gene expression, the key to the understanding of the action of BrdU lies in the elucidation of the mechanism by which BrdU destabilizes nucleosome positioning.…”
Section: Discussionsupporting
confidence: 87%
“…The N-terminal tail of histone H2B is constituted of 37 amino acid residues in S. cerevisiae [32]. The overall amino acid sequence of the histone H2B N-terminal tail (1-37) is not highly conserved among species; however, its short basic region consisting of eight amino acid residues (30)(31)(32)(33)(34)(35)(36)(37) shows high sequence conservation (Fig. 3A) [33].…”
Section: Regulation Of the Sensitivity To Brdu By The Hbr Domainmentioning
confidence: 99%
“…1F , 1G ). We compared DNA methylation levels (ONT-seq) at gene promoters overlapping with CpG islands (CGI promoters), that are associated with housekeeping genes expressed in all cell types, versus non-CGI promoters associated with genes expressed only in specific cell types and located in heterochromatin in non-expressing cell types [55]. DNA methylation at CGI promoters was uniformly low, whereas DNA methylation at non-CGI promoters showed a bimodal distribution of DNA methylation in both euchromatin and heterochromatin and this decreased significantly in Ogt iKO compared to Ctrl Ogt fl mESC ( Fig.…”
Section: Resultsmentioning
confidence: 99%